A STUDY OF GREEN INDEPENDENT VILLAGES IN ECONOMIC ASPECTS IN THE SPECIAL REGION OF YOGYAKARTA - Sugiyanto Sugiyanto; Nelly Tiurmida; Tomi Agus Triono (International Journal of Social Science, 2022)
Independent green village is a village that can develop and enhance their institutional capacity by persevering their tradition, local wisdom, and knowledge. This village is expected to be able to develop their economical products that are based on natural resources and is managed sustainably so that it can be a way to maximize the village’s prosperity. This study uses qualitative exploratory research with Strength, Weakness, Opportunity, and Threat (SWOT) as its analytical tool. The data are gathered with four techniques, that is observation, interview, documentation study, and Focus Group Discussion (FGD). Informants are determined interactively and continuously so that it produces saturated data. The result of this exploratory study found that people and the natural environment in the economic sector are united and are interrelated. Hence, the economic access of the independent green village can improve the natural resources quality through community empowerment, skill development, knowledge on entrepreneurship improvement, and expanding business relationship through driving figures like innovator that has concern regarding people to improve and diversify local resources-based products.